2002
DOI: 10.1103/physrevlett.88.105901
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Photoelectron Spectroscopy Study of Disordering inGd2(Ti1xZr

Abstract: The dramatic increases in ionic conductivity in Gd2(Ti1-xZrx)2O7 solid solution are related to disordering on the cation and anion lattices. Disordering in Gd2(Ti1-xZrx)2O7 was characterized using x-ray photoelectron spectroscopy (XPS). As Zr substitutes for Ti in Gd2Ti2O7 to form Gd2(Ti1-xZrx)2O7 (0.25 < x < or =0.75), the corresponding O 1s XPS spectrum merges into a single symmetric peak. This confirms that the cation antisite disorder occurs simultaneously with anion disorder. Furthermore, the O 1s XPS spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
2
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 19 publications
4
38
2
2
Order By: Relevance
“…The cation and anion substructures in the Gd 2 ͑Ti 1−y Zr y ͒ 2 O 7 solid solution disorder gradually as the Zr content increases, leading to the appearance of oxygen vacancies at 48f sites which are known to be responsible for oxygen hopping and diffusion. 5,9 Correspondingly, a marked increase in oxygen conductivity is observed in this system when y ജ 0.3, which has been related to the onset of the anion disordering. 9 Mechanical milling allows preparing partially disordered and metastable RE 2 Ti 2 O 7 pyrochlores, 10 obtained otherwise only by chemical substitution, ion irradiation, or pressureinduced compression.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The cation and anion substructures in the Gd 2 ͑Ti 1−y Zr y ͒ 2 O 7 solid solution disorder gradually as the Zr content increases, leading to the appearance of oxygen vacancies at 48f sites which are known to be responsible for oxygen hopping and diffusion. 5,9 Correspondingly, a marked increase in oxygen conductivity is observed in this system when y ജ 0.3, which has been related to the onset of the anion disordering. 9 Mechanical milling allows preparing partially disordered and metastable RE 2 Ti 2 O 7 pyrochlores, 10 obtained otherwise only by chemical substitution, ion irradiation, or pressureinduced compression.…”
Section: Introductionmentioning
confidence: 90%
“…4,5 Pyrochlore oxides A 2 B 2 O 7 are a very large family of compounds showing a great variety of physical and chemical properties as a function of chemical composition and the existing atomic ordering ͑disordering͒ and oxygen vacancies. Thus, while some pyrochlores such as Gd 2 Zr 2 O 7 are electronically insulating and fast high-temperature ionic conductors, others such as Gd 2 Mo 2 O 7 display at room temperature a metallic conducting behavior.…”
Section: Introductionmentioning
confidence: 99%
“…En este trabajo se presentan datos de conductividad ac de varios circonatos conductores de iones oxígeno de fórmula general Gd 2 (Zr y Ti 1−y ) 2 O 7 , los cuales presentan una estructura de tipo pirocloro con un alto grado de desorden estructural y que han demostrado ser materiales prometedores para sustituir a fluoritas tales como la circonia estabilizada con itria como electrolito sólido en celdas de combustible cerámicas (21,22). Estructuralmente, los óxidos de este tipo se relacionan con la fluorita y como ésta, presentan conductividades considerables a elevadas temperaturas.…”
Section: Boletín De La Sociedad Española De Cerámica Y Vidriounclassified
“…These materials present a highly disordered pyrochlore structure and have been shown to be promising candidates to substitute fluorites such as yttria-stabilized zirconia as the electrolyte currently used in fuel cells. 21,22 The cation and anion substructures in the Gd 2 ͑Zr y Ti 1−y ͒ 2 O 7 solid solution disorder gradually as the Zr content increases, leading to the appearance of oxygen vacancies at 48f sites which are known to be responsible for oxygen hopping and diffusion. 22,23 We show that the crossover to the NCL behavior can be clearly identified in these materials and it is found to be thermally activated with an activation energy E NCL much lower than the activation energy E dc for the dc conductivity.…”
Section: ͑1͒mentioning
confidence: 99%
“…21,22 The cation and anion substructures in the Gd 2 ͑Zr y Ti 1−y ͒ 2 O 7 solid solution disorder gradually as the Zr content increases, leading to the appearance of oxygen vacancies at 48f sites which are known to be responsible for oxygen hopping and diffusion. 22,23 We show that the crossover to the NCL behavior can be clearly identified in these materials and it is found to be thermally activated with an activation energy E NCL much lower than the activation energy E dc for the dc conductivity. We found that the values of E NCL do not change upon modifying composition unlike those of E dc , and, in fact, E NCL is similar to the energy barrier of the cages, E a , as calculated from computer simulations 24 and also estimated from electrical conductivity relaxation measurements at higher temperatures.…”
Section: ͑1͒mentioning
confidence: 99%